Compliance study of hip protector users for prevention of fragility fracture: A pilot randomized trial. Issue 4 (14th August 2022) - Wong, Man Sang; Wu, Hui Dong; Beygi, Babak Hassan; Zhang, Qian; Lin, Yangmin; Chan, Wing Sheung; Lou, Edmond
Abstract : Background: Hip protectors have been widely used for hip fracture prevention in the elderly, but its efficacy remains controversial. Users' compliance to hip protector is an important factor for its efficacy. However, the assessment of users' compliance tended to be subjective and unreliable in the past. Objectives: To quantify the elderly's compliance to hip protectors and investigate the effect of different underpant designs on the elderly's compliance. Study Design: A pilot randomized trial. Methods: Thirty-one participants were recruited and provided with hip protectors in which compliance monitors were installed and delivered with three pairs of either the conventional underpants or the purpose-design underpants randomly. Participants were encouraged to use the hip protectors with the assigned underpants for whole day. After 4 weeks, compliance data were downloaded from the compliance monitors. Participants were also asked to fill a survey form for acceptance analysis. The Spearman correlation coefficient and the Wilcoxon signed-rank test/2 independent samples t test/Mann-Whitney U test were used for the corresponding statistical analyses. Results: Thirty-one participants were recruited initially. Eighteen participants were excluded from instrumented compliance analysis because of limited or no data collection. The data of the resting 13 participants (six in the conventional underpants group and seven in purpose-design underpants group) were analyzed and showed an average instrumented compliance of 77.5% which was lower than the average self-reporting compliance (83.3%) of all the available 23 participants (eight of 31 became wheelchair-bounded). Participants' compliance was positively correlated with their acceptance to the hip protectors and significantly higher in the purpose-design underpants group than in the conventional underpants group ( P < 0.05). Conclusions: This pilot study demonstrated a feasible protocol for compliance quantification of the elderly to the hip protectors, the importance to have an objective compliance measure to assess users' actual compliance, and purpose-design underpants could improve the users' compliance. Future studies with long-term observation and large sample size deserve further proof of the current findings.